INTERNAL STRATEGY ANALYSIS OF THE COMPANY USING THE RESOURCE-BASED VIEW (RBV) AND VALUE CHAIN APPROACHES: A CASE STUDY OF PT INDUSTRI JAMU DAN FARMASI SIDO MUNCUL TBK. - Ackhriansyah Ahmad Gani; Nazwar M Saimima; Azwar Jayanegara (Journal Informatic, Education and Management (JIEM), 2026)
Intense competition in the modern herbal medicine industry requires companies to optimize internal capabilities to maintain their position as market leaders. This study aims to dissect the internal strategy of PT Industri Jamu dan Farmasi Sido Muncul Tbk. in identifying core competencies and building a sustainable competitive advantage. The method used is descriptive qualitative with a case study approach. Data sources obtained from secondary data (company's annual reports and literature reviews) were analyzed using the Resource-Based View (RBV/VRIO) framework and Value Chain Analysis. Value Chain analysis shows strong value creation in primary activities, particularly inbound logistics through local farmer partnerships and automated production operations. VRIO analysis proves that Tolak Angin's brand equity, modern R&D facilities, and pharmaceutical certifications (CPOB/CPOTB) are strategic resources that meet the criteria for a sustainable competitive advantage. However, an internal weakness was found regarding revenue dependence on a single dominant product. Sido Muncul's competitive advantage relies on pharmaceutical quality standardization and brand strength. The company is advised to aggressively implement product diversification to mitigate the risk of product dependency.